The Economics of Happiness: Tourism Development, Neocolonialism and Marginalization in Local Traditional Communities - Intan Purwandani (Gadjah Mada Journal of Tourism Studies, 2018)
This scienti c article takes as a starting point a series of studies done by anthropologist Helena Norberg-Hodge which resulted in the documentary “The Economics of Happiness” which explains the interrelation between globalization, economics, and happiness among a society. Through a study case in the Indian community of Ladakh, Norberg-Hodge witnesses with her own eyes the negative repercussions of globalization as a force which disintegrated the self-subsistence structure and undermined alternative ways of development other than the Westernized pro t oriented understanding of the concept. The main objective of the present article is therefore to analyze the globalization phenomenon as a neocolonial movement and how this has resulted in economic and social forms marginalization for traditional rural communities where tourism development has arisen. By analyzing two case studies in former colonized areas that are now touristic destinations, we nd empirical evidence supporting our main argument. It has been found that globalization is indeed a movement lead by apparent neoliberal principles which promote global integration and promise economic development to Third World Nations, but in reality, it results in an asymmetrical situation in which Western developed countries reap more bene t out of it than developing nations. Furthermore, local communities are economically and socially marginalized within their own localities.